Outcome of patients with and poor prognostic factors for Mycobacterium kansasii-pulmonary disease. (May 2019) - Liu, Chia-Jung; Huang, Hung-Ling; Cheng, Meng-Hsuan; Lu, Po-Liang; Shu, Chin-Chung; Wang, Jann-Yuan; Chong, Inn-Wen
Abstract: Background: Aggressive therapy for Mycobacterium kansasii -pulmonary disease (MK-PD) is recommended because of the virulence of MK. However, some clinicians may be concerned regarding the lengthy course and numerous adverse effects. This study evaluated the natural course of MK-PD and investigated its prognostic factors. Methods: Radiographic outcome, prognostic factors, and mortality within 1 year for MK-PD were obtained from patients in 6 hospitals in Taiwan from 2010 to 2014 (derivation cohort) and validated using patients in 2015 and 2016 (validation cohort). Results: Of the 109 patients with MK-PD in the derivation cohort, radiographic progression occurred in 70 (64%), with a 1-year mortality rate of 43% and median survival of 71 days, whereas none of the 39 cases without radiographic progression died. All patients with acid-fast smear (AFS) grade ≥ 3 experienced radiographic progression. For the others, the independent risk factors of radiographic progression were fibroC avitary pattern, L eucocyte count >9000/μL, O ld age (age >65 years), pU re MK in sputum (no other mycobacteria), and no D iabetes mellitus (the CLOUD factors). By applying these criteria to the validation cohort (n = 112), 3 (9%) of the 33 patients with MK-PD who initially had AFS grade < 3 and < 3 CLOUD risk factors experienced radiographic progression, and none of the 3 died of MK-PD. Conclusions: Because of the high risk of radiographic progression and subsequent fatal outcome, immediate anti-MK treatment is recommended. For patients with MK-PD who have sputum AFS grade <3 and < 3 CLOUD risk factors, regular follow-up may be an alternative. Highlights: Two-thirds of patients with MK-PD experience radiographic progression within 1 year. One-year mortality rate was approximately 40% once radiographic progression occurred. Predictors of radiographic progression included AFS grade ≥3 and presence of ≥3 CLOUD risk factors. Aggressive treatment is recommended for patients with MK-PD. Regular follow-up may be an alternative for those without predictors of radiographic progression.